Inherited Abnormalities of Platelets - Nurden, Alan T. (Thrombosis and Haemostasis, 1999)
Genetic defects of platelets give rise to bleeding syndromes of varying severity. Affected areas of platelet function include the glycoprotein (GP) effectors of adhesion and aggregation, primary receptors for agonists, signaling pathways where messages are transmitted to targets elsewhere in the membrane or within the platelet, dense- and α-granule secretion, ATP production, and the expression of procoagulant activity. Glanzmann thrombasthenia (GT) and Bernard-Soulier syndrome (BSS) are the best-characterized platelet diseases and will have a major place in this review. GT is caused by abnormalities of platelet membrane GP IIb-IIIa (integrin αIIbβ3), resulting in absent platelet aggregation. BSS is caused by abnormalities of the GP Ib-IX-V complex, resulting in a loss of platelet adherence to vessel wall subendothelium. The disorders affecting platelet morphology, which give rise to the so-called giant platelet syndromes, are also considered.Studies on platelet disorders are significant because the knowledge gained has provided a better understanding of the molecular basis of primary hemostasis and has helped in the development of new drugs for use in antithrombotic therapy. In 1987, this author gave the inaugural State-of-the-Art lecture at an International Society of Thrombosis and Haemostasis meeting.1 At that time, the application of molecular biology procedures to the study of platelet disorders was just beginning. Now, 12 years later, some of these data will be reviewed and the recent advances discussed.